Development of E-module Food Chemistry Constructivism-Based 5-Phase Needham - A. Rachman Ibrahim; Andi Suharman; Diah Kartika Sari (Postgraduate, University of Mataram, 2022)
This study aims to produce a valid and practical e-module of food chemistry constructivism based 5-phase Needham's. This research is development research with ADDIE development model combined with Tessmer formative evaluation. The stages of ADDIE development used in this study include the analysis stage, the design stage, and the development stage only, which then proceeds to the Tessmer formative evaluation stage which includes expert review, one to one, and small group. At the expert review stage, the e-module food chemistry was validated by experts from the fields of pedagogic experts, material experts and design experts. The results of the validation assessment scores obtained at the expert review stage in the pedagogic field are 0.848 (high), the material field is 0.895 (high), and the design field is 0.889 (high). This shows that the e-module constructivism based 5-phase Needham's that has been developed is valid. The practicality of the e-module constructivism based 5-phase Needham's is seen from the practicality questionnaire scores at the one-to-one stage and the small group stage. The one to one stage resulted in a score of 0.865 (high) and in the small group stage it was 0.865 (high), which means that the e-module based constructivism 5-phase Needham has been practically developed